A Case of Pill-Induced Esophagitis With Mucosal Dissection. Issue 3 (1998) - Adachi, Wataru; Watanabe, Hiroyuki; Yazawa, Kazuyuki; Koide, Naohiko; Koike, Shoichiro; Amano, Jun; Tamai, Chisato
Abstract : With the advance of gastrointestinal endoscopy, pill-induced esophagitis has been detected more frequently, but the association of mucosal dissection is rare. We reported a case of pill-induced esophagitis associated with mucosal dissection. A 66-year-old male with combined valvular heart disease was admitted for cardiac surgery. Cefotiam hydrochloride tablet was administered for postoperative wound infection of cardiac surgery. Next morning severe odynophagia and retrosternal pain were occurred. Upper gastrointestinal endoscopy performed 2 days after onset of the symptom showed detached mucosa at the upper thoracic esophagus and acute esophagitis at middle and lower thoracic esophagus. Histological examination of the mucosa revealed that the esophageal mucosa was detached from the lamina propria. After the treatment for esophagitis, almost normal esophageal mucosa covered the esophagus without scarring or stricture. The present case was diagnosed as cefotiam hydrochloride tablet induced esophagitis because of the onset of this disease. Mucosal dissection of the esophagus may be associated with both the esophagitis and bleeding tendencies caused by anticoagulant therapy.